1996
DOI: 10.1159/000237299
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Leukotriene Synthesis by Honokiol in Rat Basophilic Leukemia Cells

Abstract: The effects of honokiol, a diphenyl compound extracted from a Chinese herbal medicine, on leukotriene (LT) synthesis were evaluated in rat basophilic leukemia (RBL) cells. The production of LTC4 and LTB4 stimulated by the Ca2+ ionophore A23187 was measured in RBL-1 cells by high-performance liquid chromatography. Honokiol inhibited the production of LTC4 and LTB4 stimulated by A23187 in RBL-1 cells. Honokiol did not inhibit either phospholipase A2 activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Honokiol is reported to have various activities, including anti-oxidative, anti-inflammatory, anti-allergic, anti-angiogenic and anti-tumor properties. [10][11][12][13][14][15] Previous reports have shown that honokiol inhibits nitric oxide production by lipopolysaccharide-activated RAW264 cells 24) and mouse macrophages. 25) Recently, honokiol has been shown to potentiate TNF-a-induced apoptosis in chronic myelogenous leukemia KBM5 cells, suppress TNF-a-induced tumor cell invasion, and inhibit RANKLinduced osteoclastogenesis in RAW264 cells, although the mechanism of action of honokiol on osteoclastogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol is reported to have various activities, including anti-oxidative, anti-inflammatory, anti-allergic, anti-angiogenic and anti-tumor properties. [10][11][12][13][14][15] Previous reports have shown that honokiol inhibits nitric oxide production by lipopolysaccharide-activated RAW264 cells 24) and mouse macrophages. 25) Recently, honokiol has been shown to potentiate TNF-a-induced apoptosis in chronic myelogenous leukemia KBM5 cells, suppress TNF-a-induced tumor cell invasion, and inhibit RANKLinduced osteoclastogenesis in RAW264 cells, although the mechanism of action of honokiol on osteoclastogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activities of these compounds include potent inhibition of lipid peroxidation (Lo et al, 1994;Haraguchi et al, 1997). scavengers of hydroxyl radicals (Taira et al, 1993), inhibition of leukotriene synthesis in leukaemia cells (Hamasaki et al, 1996) and inhibition of UV-induced mutations (Fujita and Taira, 1994). They are considered to be important active components of medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Baillon (Wu Wei Zi, Magnolia Vine, Schisandraceae) is a plant commonly used in traditional Chinese medicine and also widely used in Russia, possessing various biological activities like antihepatotoxic, antibacterial and cardiovascular effects, as well as effects on CNS, uterus and immune regulatory actions. 1,2 The fruits of Schisandra chinensis are a rich source of lignans with concentrations ranging from 7.2% to 19.2% depending on the geographical origin and on the harvesting time. 3 Main constituents such as schisandrin (1), gomisin A (2), angeloylgomisin H (3), and tigloylgomisin H (4), which contain a dibenzo[a,c]cylooctadiene skeleton with a high degree of methoxylation/dioxomethylene bridges at the biphenyl system have been isolated and fully characterized by the group of Ikeya.…”
Section: Introductionmentioning
confidence: 99%
“…18 Biphenyl-neolignans such as magnolol and honokiol and derivatives thereof have been shown to act as potent inhibitors of COXisoenzymes and 5-LOX. [19][20][21][22] In these compounds the biphenyl axis is more or less flexible, whereas in S. chinensis lignans this torsion angle is fixed by the presence of a cyclooctadiene ring. Apart from some reports indicating minor activities, no detailed studies revealing significant activity of Schisandra lignans and related structures on COX/LOX were carried out to date to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%